Dithered sweep lengths - A new technique for attenuating harmonic noise in vibroseis data - Dean, Tim; Iranpour, K.; Clark, M.; Poole, A. (2016)
A significant drawback of the use of hydraulic vibrators as the source for land seismic surveys is the contamination of their transmitted signal with harmonics. The variphase technique involves transmitting multiple sweeps with different initial phases. After the records are stacked together the harmonics are attenuated. In this paper we describe an alternate approach which involves stacking sweeps with slightly varying (dithered) lengths. The efficiency of the technique improves as the number of sweeps and the range of sweep lengths are increased. Ideally, the sweep lengths should be regularly spaced rather than randomly selected. Overall, the technique is not as effective as variphase, although the difference is relatively minor. However, the dithered sweep-length technique does have advantages in that it is not sensitive to missing sweeps, and it offers the ability to reduce harmonics if phase rotation is not possible.